The Implementation Steps of Project-based Learning in English Language Teaching at Islamic Boarding School - Yamin, Muhammad; Halim, Abd.; Muhayyang, Maemuna (Celebes Journal of Language Studies, 2023)
Project-based learning is a student-centered method of organizing learning in projects in which the students drive their learning and the teacher plays as facilitator in a project designed. This research aimed to explore the implementation steps of the Project-Based Learning (PjBL) approach employed by a teacher in an EFL classroom. It used a descriptive qualitative method. For the description of PjBL steps, the researchers administered classroom observation and in-depth interviews taking an English teacher as the informant at Al Ihsan Islamic boarding School, Polewali Mandar, West Sulawesi. The findings revealed that the teacher implemented three major steps of PjBL in English language teaching, that is (1) planning and preparation, (2) the project work, and (3) report and presentation. Planning and preparation steps showed the best sample of previous project work referring to a real-life example of language usage and building the project activities’ framework; the project work step guided the project’s implementation and monitored the progress of the students’ project; and report and presentation step bridged the discussion and encouraged peer assessment among the students’ work. Based on these three steps, it is concluded that the implementation of PjBL had a positive impact not only on English language learning as a whole but also on other areas of learning, that is critical thinking, collaboration and communication skills of the students as well.